2013
DOI: 10.1007/s10120-013-0319-x
|View full text |Cite
|
Sign up to set email alerts
|

Naso-gastric or naso-jejunal decompression after partial distal gastrectomy for gastric cancer. Final results of a multicenter prospective randomized trial

Abstract: Background Only a few, small, monocentric randomized controlled trials (RCTs) have compared routine vs. no placement of a nasogastric or nasojejunal tube decompression (NG/NJT) in patients undergoing partial distal gastrectomy (PDG) for gastric cancer. However, to our knowledge, no multicenter prospective RCT has analyzed the role of decompression after both the Billroth II (BII) procedure and Roux-en-Y (RY) gastrojejunostomy.The aim of this study was to determine whether NG/NJT prevents the consequences of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…Our search for papers on nasogastric/nasojejunal decompression for gastrectomy published in or after 2014 showed two RCT and two meta‐analyses . These papers strongly supported the recommendation of the guidelines.…”
Section: Consensus Guidelines For Enhanced Recovery After Gastrectomysupporting
confidence: 53%
“…Our search for papers on nasogastric/nasojejunal decompression for gastrectomy published in or after 2014 showed two RCT and two meta‐analyses . These papers strongly supported the recommendation of the guidelines.…”
Section: Consensus Guidelines For Enhanced Recovery After Gastrectomysupporting
confidence: 53%
“…One commonly used parameter is the time to first flatus. Varied results were reported regarding whether NGT shortens the time to first flatus [18]. Our data, in accordance with the meta-analyses [3,19] and the prospective randomized controlled trial [10], showed no effect in this regard.…”
Section: Discussionsupporting
confidence: 80%
“…Although oral feeding at POD1 was linked to mortality on univariate analysis, our small sample size prevented any definitive conclusions. Indeed, the gastric tube is no longer used postoperatively in scheduled surgery as the tube itself can provoke adverse events 6,9‐11 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the gastric tube is no longer used postoperatively in scheduled surgery as the tube itself can provoke adverse events. 6,[9][10][11]…”
Section: Prevention Of Poapmentioning
confidence: 99%